Preemptive analgesia of dexamethasone as compared to ketorolac tromethamine in simple tooth extractions - Carneiro,Rodrigo Mathias Freire de Menezes (2014)
BACKGROUND AND OBJECTIVES:Understanding that pain is the most important postoperative problem, in face to the need of establishing a therapeutic protocol to control post-tooth extraction pain and due to few studies comparing these drugs is that our study is justified. This study aimed at evaluating and at comparing the preemptive analgesic effect of two drugs, both administered in bolus.METHODS:This is an experimental research as from a clinical trial with human beings. It is a double-blind, crossover and randomized trial with 51 patients seen by the Oral Surgery Ambulatory of the Dentistry Department, Federal University of Sergipe (DOD/UFS), between September 2011 and September 2012, who needed simple alveolar extractions in different hemiarcades, using dexamethasone (4mg) or ketorolac tromethamine (10mg), one hour before surgery distinctively. Pain was evaluated in the first 24 and 48 hours with the visual analog scale. The interval of eight days was established between extractions.RESULTS:There have been no statistically significant differences by Fisher (p>0.05) and Friedman (p>0.05) Exact tests, or between drugs (considering a same period) or between periods (considering the same drug).CONCLUSION:There are no significant differences between drugs and observed periods.